Â¬PENGARUH CURRENT RATIO, NET PROFIT MARGIN, DEBT TO EQUITY RATIO DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN INDUSTRI MANUFAKTUR YANG GO PUBLIK DI BURSA EFEK INDONESIA - Andika Arya Lisaholet, 10.05.51.0094 (Students Journal of Economic and Management, 2014)
The objective of the study is to examine the effect of CR, NPM, DER and EPS on Stock Prices in industry manufacturing company is go public in Indonesian Stock Exchange. The research was conducted again because that empirical evidence were linked with fundamental factors with stock prices still showed the different results that need further research to prove how the influence of fundamental factor on stock prices especially the industry manufacturing sector in Indonesian Stock Exchange. This study was taken because there are still differences between the research study with each other. This research was conducted using secondary data. Population in this research was industry manufacturing company obtained from share which was listed and âgo publicâ in Indonesian Stock Exchage period 2008-2011. Sampling technique used was purposive sampling. There is 65 companies that can be analysed. This study is analyzed by using multiple regression.The multiple regression shows that CR, NPM and EPS have significant positive effect on stock prices, while DER havenât significant positive effect on stock price. Adjusted R Square value of 0,877 can illustrate that the dependent variable is explained by the independent variable variabelitas for 87,7%, while 12,3% are influenced by the other variables. Keywords: Stock Price, Current Ratio, Net Profit Margin, Debt to Equity Ratio, and Earning Per Share